Artificial Intelligence as a driver of digital competency development in university students - Velásquez-Correa, Carlos Daniel (2025)
The purpose of this study was to determine the impact of artificial intelligence (AI) on the development of digital competencies among university students. The research employed a quantitative approach with a descriptive–correlational level, using a non-experimental and cross-sectional design. The population consisted of students enrolled in the 2024-II semester at the National University Toribio Rodríguez de Mendoza of Amazonas (UNTRM), with a sample of 400 participants selected through non-probability sampling. Data were collected using two structured Likert-scale questionnaires: one assessing students’ perception and use of AI tools (23 items), and another measuring their level of digital competencies (20 items). The findings revealed that 51.5% of students demonstrated a high level of AI tool usage, while 50.5% reached a medium level of digital competencies. A significant, positive, and moderately strong correlation was found between both variables (Spearman’s Rho = 0.639; p < 0.001), indicating that greater use of AI is associated with better development of digital competencies. It was concluded that artificial intelligence serves as an influential factor in strengthening university students’ digital skills, highlighting the need to integrate these technologies into higher education learning processes.